Communication Law in Marketing: Paradigms in maintaining Corporate Identity, Reputation and Brand Image - Iing Saefudin (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to analyze the role of communication law in marketing as a paradigm that functions to maintain corporate identity, reputation, and brand image. Effective and legal communication is an important element for a company's success in building a strong and sustainable image amidst increasingly tight business competition. This study uses a normative legal research method based on literature studies and analysis of regulations related to marketing communications such as the Electronic Information and Transactions Law. The research results show that the law of effective communication in marketing, summarized in the concept of REACH (Respect, Empathy, Audible, Clarity, and Humble), is very important for building strong relationships between companies and consumers. Respecting and understanding the consumer perspective, and ensuring that messages are delivered clearly and humbly, can increase understanding, trust, and loyalty. In Indonesia, marketing communications are regulated by Law No. 1 of 2024 concerning the Second Amendment to Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE LawITE law), which emphasizes transparency, accuracy, and ethics. Compliance with the ITE Law, which prohibits defamation, the spread of fake news, the use of personal data without permission, and the presentation of deceptive data, helps companies build a good reputation and maintain positive relationships with consumers. Overall, communication law not only protects consumers but also serves as a strategic tool for companies to achieve sustainability and growth in a competitive market